Using synchronous reinforcement to increase mask wearing in adults with intellectual and developmental disabilities. Issue 4 (3rd August 2022) - McHugh, Catherine L.; Dozier, Claudia L.; Diaz de Villegas, Sara C.; Kanaman, Nicole A.
Abstract : In 2020 the Centers for Disease Control provided the public with recommendations to slow the spread of COVID‐19 by wearing a mask in the community. In the current study, experimenters coached group home staff via telehealth to implement synchronous schedules of reinforcement to increase mask wearing for 5 adults with intellectual and developmental disabilities. Results showed the intervention effectively increased mask wearing for all participants for up to 30 min. Additionally, some participants for whom we assessed generalization of mask wearing demonstrated generalization to various community environments. Furthermore, procedural integrity data suggested staff could be coached via telehealth to implement the intervention, and staff surveys suggested the procedures and coaching were socially valid.